The influence of family support, school environment, and coping strategies on the self-identity dev elopment of adolescents in government-affiliate school - Kumoro, Retno; Herawati, Tin; Sumarwan, Ujang; Muflikhati, Istiqlaliyah (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
This study aims to analyze the influence of family support, school environment, and coping strategies on the self-identity development of cadets in government-affiliate school. A quantitative approach with an explanatory design and survey method was used, involving 331 cadet respondents from levels I and II, aged 18 to 21, at a vocational school under the Ministry of Transportation. The instrument used was a standardized questionnaire to measure the variables of family support, school environment, coping strategies, and the self-identity development. Data were analyzed using Structural Equation Modelling-Partial Least Square (SEM-PLS). The results of the study indicate that family support, school environment, and coping strategies have a significant positive effect on the self-identity development. Family support plays a crucial role in personal development and future planning, while a supportive school environment, characterized by positive relationships between teachers and peers, accelerates the self-identity development. Furthermore, effective coping strategies assist in managing stress and life challenges more effectively. These findings emphasize the importance of family support, school environment, and coping strategies in supporting the personal development of cadets in government-affiliate school. The implications of this study suggest that the government should support inclusive educational policies, train teachers to address the emotional and social needs of cadets, and encourage further research on coping strategies and mental health in the context of vocational education.